Pengaruh Penggunaan Model Discovery Learning Terhadap Keterampilan Membaca Pemahaman Teks Berita Siswa Kelas VII UPT SMP Negeri 2 Bayang - Alifa Salsabilla; Andria Catri Tamsin; Nursaid Nursaid; Dewi Anggraini (Universitas Pakuan, 2026)
THE EFFECT OF THE USE OF THE DISCOVERY LEARNING MODEL ON THE READING AND COMPREHENSION SKILLS OF NEWS TEXTS OF GRADE VII STUDENTS UPT SMP NEGERI 2 SHADOW The low reading comprehension skills of seventh-grade students at UPT SMP Negeri 2 Bayang are the background of this research. The main problems include students' difficulties in understanding explicit and implicit information, as well as their low ability to draw conclusions from the texts they read. This study aims to analyze the effect of the discovery learning model on news text reading comprehension skills. The research method used was a pre-experiment with a One-Group Pretest-Posttest design. The research sample consisted of 26 seventh-grade students selected through a purposive sampling technique. The research instrument was an objective test of news text reading comprehension skills. The results of data analysis showed a significant increase in the average score from 72.16 (More than Sufficient) in the pretest stage to 92.49 (Very Good) in the posttest stage. Hypothesis testing using a t-test showed that t count > t table at a significance level of 0.05. These results are supported by the N-Gain value which is in the high category. These findings demonstrate that the discovery learning model has a significant impact on optimally improving students' news text reading comprehension skills.